Influence des maladies infectieuses sur la production laitière des bovins laitiers. Cas des levures et moisissures - BENATTIA, Nabil (My University, 2023)
Fungi are responsible for the spoilage of various food products. They are also capable of producing several mycotoxins which represents a serious risk to human and animal health. The enumeration of fungal diversity is one of the most effective means that makes it possible to enhance it through applications in different fields. The objective of our study is the research and enumeration of the fungal flora. For this, two samples of raw milk, two samples of the “Klila” type cheese are used. The origin of these samples is the Wilaya of El Bayedh. Macroscopic and microscopic analyses make it possible to observe the fungal genera present in these samples. The results are obtained after isolation and purifications on OGA medium. According to the results, the estimated fungal flora in the cheese samples is 3,5 105 UFC/g and 156,6. 105 UFC/g, respectively for samples F1 and F2. For the L1 and L2 milk samples, the number is 163.10 5 UFC/g and 1.105 UFC/g respectively.
Keywords: Fungal diversity; Klila cheese; milk